2007
DOI: 10.1007/s10557-007-6027-1
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis and Oxidant Stress: The End of the Road for Antioxidant Vitamin Treatment?

Abstract: Extensive experimental data have revealed a central role for oxidative stress in atherogenesis and suggested a potential role for 'antioxidant' treatment in cardiovascular disease (CVD) [1-11]. Experimental data, however, have not translated into clinical benefit: most antioxidant vitamin trials have failed to reduce cardiovascular morbidity and mortality [12]. Moreover, recent clinical trials have suggested that mono-therapy with certain antioxidant vitamins like vitamin E may, in fact, be detrimental [13]. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 149 publications
0
43
0
1
Order By: Relevance
“…ROS and reactive nitrogen species are not just harmful but also vital to cell function, and some clinical trials demonstrated even augmented mortality after anti-oxidant treatment (31)(32)(33). Hence, the outcome of anti-oxidant treatment depends on the overall context, the cell type, efficient targeting, and the nature of the radical species and its detoxification product.…”
Section: Discussionmentioning
confidence: 99%
“…ROS and reactive nitrogen species are not just harmful but also vital to cell function, and some clinical trials demonstrated even augmented mortality after anti-oxidant treatment (31)(32)(33). Hence, the outcome of anti-oxidant treatment depends on the overall context, the cell type, efficient targeting, and the nature of the radical species and its detoxification product.…”
Section: Discussionmentioning
confidence: 99%
“…Phytochemicals can inhibit oxidative stress and inflammation by scavenging reactive oxygen species and reactive nitrogen species. 3 Because not only fruits and vegetables contribute to dietary antioxidants, it is important to study the overall effect from all antioxidants in the diet. The total antioxidant capacity (TAC) aims to measure the free radical-reducing capacity of all antioxidants in the diet and takes into account synergistic effects between substances.…”
mentioning
confidence: 99%
“…In diabetic rats the elevation observed in uric acid level could be due to the increased abundance and activity of xanthine oxidase. It was responsible for the formation of uric acid and also serves as an important biological source of ROS (superoxide) that contribute to oxidative damage involved in many pathological processes such as diabetes, atherosclerosis, cancer and aging [29][30][31]. Moreover, decreasing levels of HbA1c observed in (D+C2) group can reduce the risk of lipid peroxidation [32].…”
Section: Discussionmentioning
confidence: 99%